The Effects of Endothelial Cells-Preserving Technique on Microsurgical Vascular Reconstruction in Biliary Tract Malignancy: Report of Twenty Cases - Miyagi, Shigehito (S. Karger AG, 2014)
We describe our experience of resectional surgery with microsurgical reconstruction of the hepatic arteries in 20 cases with biliary tract malignancy. Hepatic artery thrombosis (HAT) is a lethal complication; therefore, it is important to perform microsurgical reconstruction safely. Recently, we adopted the back wall support suture technique with double needle sutures that does not require the damaged short arteries to be turned over. In this technique, each stitch is placed from the inner side to the outer side to keep endothelial cells. The purpose of this study was to develop safety methods. From 2003 to 2012, 20 patients with biliary tract malignancy with possible involvement of the hepatic arteries underwent resectional surgery with microvascular reconstruction (cholangiocarcinoma: n = 15; others: n = 5). For this cohort study, patients were divided into two groups: group I (n = 5) included patients who underwent the conventional ‘twist technique’ and group II (n = 15) included patients who underwent the microsurgical back wall support suture technique with double needle sutures and received gabexate mesilate, a strong serine protease inhibitor (40 mg/kg/day) for 7 days. We investigated HAT using Doppler ultrasonography for 10 days. No postoperative mortality was observed. The incidence of HAT was only one case in group I, and there was no significant difference between the two groups. However, the value of the pulsatile index and acceleration time were significantly improved in group II. In conclusion, the back wall support suture technique with gabexate mesilate administration during microvascular reconstruction was found to be safe. It is important to keep endothelial cells healthy for microvascular reconstruction.